2013
DOI: 10.1155/2013/864141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Treatments of Montmorillonite Nanoclay on Cure Behavior of Diglycidyl Ether of Bisphenol A Epoxy Resin

Abstract: Diglycidyl ether of Bisphenol A (DGEBA) based SC-15 epoxy resin was modified with three different commercially available montmorillonite (MMT) nanoclay: Nanomer I.28E and Cloisite 10A and 30B. Cure behavior of nanocomposites was studied using a variety of techniques. Primary focus of this study was to investigate influence of different surface modifications of MMT nanoclay on rheological properties and cure behavior of SC-15 epoxy resin. By adding MMT to SC-15 epoxy resin, chemistry of the epoxy is altered lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In order to enhance filler-matrix interactions surfaces of nanoclays are modified with surfactants, which reduces Van der Waals forces between the clay layers [15][16][17]. These surfactants increase the interlayer distance and allow epoxy molecules to percolate and form different microstructures [4,15,18]. The extent of clay platelets delamination by epoxy molecule penetration results in exfoliated, intercalated, or flocculated microstructures, and subsequent particlemolecules interactions facilitate property enhancements [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to enhance filler-matrix interactions surfaces of nanoclays are modified with surfactants, which reduces Van der Waals forces between the clay layers [15][16][17]. These surfactants increase the interlayer distance and allow epoxy molecules to percolate and form different microstructures [4,15,18]. The extent of clay platelets delamination by epoxy molecule penetration results in exfoliated, intercalated, or flocculated microstructures, and subsequent particlemolecules interactions facilitate property enhancements [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [15] also conducted similar investigations and concluded that type of amine curing agent and rate of chemical reaction are key factors in the formation of exfoliated microstructure. Surface modifications and processing techniques have also been identified as key factors affecting mobility of nanoclay particles during dispersion, influencing viscosity and cure behavior, including rate of conversion (catalytic), cross-linking, and overall properties of the final composites [16,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, CLOISITE-10A is organically modified montmorillonite and the modifier is known as dimethyl, hydrogenated tallow, quarternary ammonium with concentration of 125 meq/100g. The used of surface modification is to improves the nanofiller distribution by lessen the interlayer attractive forces and overcome the filler agglomeration issues [27].…”
Section: Fig 4: Contact Angle Comparison For Xlpe/nanoclay With Watementioning
confidence: 99%
“…Surface modification and functionalization of clay helps in improving the compatibility with polymers and helps in dispersing the clay platelets in polymer matrix composites (Tcherbi-Narteh et al 2013). The clays are treated with ammonium or phosphonium ions which replace the inorganic cations present between two adjacent platelets (Alexandre and Dubois 2000;Azeez et al 2013).…”
Section: Surface Modificationmentioning
confidence: 99%